Evaluasi Mutu Hasil 4 Macam Olahan Mangga - Yuniarti Yuniarti; Wahyunindyawati Wahyunindyawati; R.D. Wijadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1993)
The objective of this research was to evaluate the quality of four kinds of mango products i.e. puree, juice-syrup, jam and dried fruit. Mango varieties used were Carabao and Pico for puree, Gedong and Kensington Apple for juice syrup making Renteng, Kidang and Nenas for jam, Gadung and Lalijiwo for dried fruit. After processing, the product was kept in storage for five moths at room temperature, and than analyzed for quality and consumer acceptability. The result showed that the puree of Carabao, juice syrup of Gedong, jam of Renteng and dried fruit Gadung were more acceptable